Serological comparison of weak D versus weakly reacting D by four different methods - Dibyajyoti Sahoo; Girija Nandini Kanungo; Rachita Behera; Partha Sarathi Jena (Asian Journal of Transfusion Science)
INTRODUCTION: Weak D red cells were defined as having a reduced amount of D antigen (formerly called “Du”) that required an indirect antiglobulin test (IAT) for detection. Weakly reacting D is those which give <2+ reactions on routine methods. The present study is sharing our experience on weak D and weakly positive anti-D in various methods. MATERIALS AND METHODS: All the blood sample of patients and blood donor, which were RhD negative, were included in the study. Furthermore, RhD positive sample <2+ was included. We repeated blood grouping of all these samples by gel card (Tulip), tube method (two different antisera), slide method, and Solid Phase Red Cell Adherence (SPRCA) (Immucore, USA). RESULTS: A total number of samples were 27,245. RhD negative found out to be 945 (3.46%). Out of all, 929 (98.3%) samples were Rh D negative in gel card and IAT negative, while 16 (1.7%) were weak D positive. Rh D typing with these samples by different antisera at four platforms showed that 14 were weakly positive (<2+) in any of the four platforms. Similarly, out of 26,300 Rh D Positive samples, 21 samples (0.079%) were serologically weak (<2+). Repeat Rh D typing was done with different antisera in all four platforms. Result showed more than 50% were Rh D negative in any of four platforms. CONCLUSION: Above observation showed that serological tests at various platforms failed to distinguish weak D from weakly reacting D. Thus, we propose that weakly reacting D should be treated equal as weak D unless they are distinguished by genotyping.